Schistosomiasis mansoni: ultrasound-evaluated hepatic fibrosis and serum concentrations of hyaluronic acid - Silva, C C (Maney Publishing, 2011)
Schistosomiasis mansoni is a fibrogenic liver disease that constitutes a major health problem in north–eastern Brazil. Although one common manifestation of the disease, periportal fibrosis (PPF), can be assessed by ultrasonography by well-trained physicians, the necessary equipment and personnel are not always readily available. Serum markers, including hyaluronic acid (HA), have been used as alternative means of measuring fibrosis. Recently serum concentrations of HA have been evaluated in 77 Brazilians (61 cases of schistosomiasis mansoni and 16 healthy controls) and compared against the ultrasound-evaluated PPF in the same subjects. The HA was measured using a non-competitive fluorescence-based assay, while the PPF was explored using a portable ultrasound scanner (SSD-500; Aloka, Tokyo) and graded, as patterns A–F, according to the World Health Organization’s ‘Niamey protocol’. In general, the serum concentrations of HA were found to be positively correlated with the severity of the PPF. The mean concentration of HA in the sera of the 16 controls was significantly lower than that recorded in the schistosomiasis cases who showed PPF of patterns D or E (P<0·001 for each). The cases who showed pattern-C PPF also had significantly less HA in their sera than the cases with PPF of patterns D or E (P<0·001 for each), and the cases with pattern-D fibrosis had significantly lower HA concentrations in their sera than the cases with PPF of pattern E (P<0·001). In an analysis based on a receiver-operating-characteristic (ROC) curve, an HA concentration of 20·2 μg/litre of serum was identified as a threshold that could be used to distinguish moderate cases of PPF (i.e. patterns C or D) from the more advanced cases (i.e. patterns E or F), with a sensitivity of 60% and specificity of 65%. In conclusion, it appears that serum concentrations of hyaluronic acid could be used as markers for periportal fibrosis in patients with schistosomiasis mansoni.